A randomized study investigating the effect of omeprazole on the pharmacokinetics of oral semaglutide. (3rd August 2018) - Bækdal, Tine A.; Breitschaft, Astrid; Navarria, Andrea; Hansen, Cilie W.
ABSTRACT: Background : Since the first oral glucagon-like peptide-1 analog comprises semaglutide co-formulated with an absorption enhancer, sodium N-(8-[2-hydroxybenzoyl] amino) caprylate, which induces a transient, localized increase in gastric pH, we have investigated whether a proton pump inhibitor affects the pharmacokinetics of oral semaglutide. Research design and methods : A single-center, randomized, open-label, parallel-group trial investigated pharmacokinetic interactions of oral semaglutide with omeprazole (40 mg once-daily) in 54 healthy subjects. Primary endpoints were area under the plasma concentration-time curve over 24 h for semaglutide (AUC0−24h, semaglutide, Day10 ) and maximum concentration of semaglutide (Cmax, semaglutide, Day10 ) at day 10. Results : Exposure of semaglutide appeared to be slightly increased, although not statistically significantly, with oral semaglutide plus omeprazole versus oral semaglutide alone (AUC0−24h, semaglutide, Day10 [estimated treatment ratio 1.13; 90%CI 0.88, 1.45] and Cmax, semaglutide, Day10 [estimated treatment ratio 1.16; 90%CI 0.90, 1.49]). Gastric pH was higher with oral semaglutide and omeprazole versus oral semaglutide alone. Adverse events were mild or moderate and, most commonly, gastrointestinal disorders. Conclusions : There was a slight non-statistically significant increase in semaglutide exposure when oral semaglutide was administered with omeprazole, but this is not considered clinically relevant and no dose adjustment is likely to be required.